PERCEPTION ON THE USE OF ZOOM IN SPEAKING CLASS OF THE THIRD YEAR STUDENTS AT TADULAKO UNIVERSITY - Muhammad Triansyah; Konder Manurung; Wahyudin Wahyudin (Tadulako University, 2022)
This study aims to know students' perceptions on the use of zoom in speaking class as an alternative solution. Whether the use of zoom as a media of online learning in speaking class is perceived positive or negative during pandemic eras of covid-19. The subjects of this research were 47 students of class 2019, the academic year 2021–2022, at Tadulako University of English Education Study Program. The research was mix method research with embedded design. The instruments used to collect data are questionnaires and interviews. The results of data analysis show that the use of zoom in speaking class perceived negatively by the student, there are many aspects influenced such as: the use of zoom application in speaking class could not fulfill the evaluation aspects of speaking skills itself, instability of internet connection interfere in the midst of knowledge transfer, financial problem in purchasing internet package, and students lack of initiative in upgrading their speaking achievement. However, there are also some positive perception that is found in this study regarding the use of zoom as a media of learning. The students agreed that the use of zoom application is helpful and could help the student learn autonomously which change their learning habit and support students to be actively engaged during speaking class. This implies that the use of the zoom application is not appropriate to be use in speaking classes. In addition, students agree that the zoom application cannot help them improve their speaking skills.